1999
DOI: 10.1038/sj.bmt.1701659
|View full text |Cite
|
Sign up to set email alerts
|

Sequential cycles of high-dose chemotherapy with dose escalation of carboplatin with or without paclitaxel supported by G-CSF mobilized peripheral blood progenitor cells: a phase I/II study in advanced ovarian cancer

Abstract: Summary:To assess high-dose carboplatin chemotherapy with or without paclitaxel with filgrastim mobilized peripheral blood progenitor cell (PBPC) support in a phase I/II study, a total of 21 patients with mostly chemonaive disease received four cycles of high-dose chemotherapy. Cycle 1 (cyclophosphamide, 6 g/m 2 ) was followed by two cycles of carboplatin (1600 mg/m 2 or 1800 mg/m 2 ). Cycle 4 consisted of carboplatin (1600 mg/m 2 ), etoposide (1600 mg/m 2 ), and melphalan (140 mg/m 2 ). Further chemotherapy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 32 publications
0
21
2
Order By: Relevance
“…Earlier studies had shown that carboplatin is toxic at a dose of (100-200 mg/kg, intraperitoneally) to rats (Kimura et al 1989;Nonclercq et al 1989;Haragsim & Zima, 1992;Blommaert et al 1996;Husain et al 2001). These doses are equivalent to the clinical therapeutic doses of carboplatin in cancer patients (Bishop 1992;Bohm et al 1999;Wandt et al 1999;Maldoon et al 2000). However, administration of high and/or cumulative doses of carboplatin produced renal toxicity in humans (Agraharkar et al 1998;English et al 1999) and experimental animals (Ueda et al 1991;Martinez et al 1993).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier studies had shown that carboplatin is toxic at a dose of (100-200 mg/kg, intraperitoneally) to rats (Kimura et al 1989;Nonclercq et al 1989;Haragsim & Zima, 1992;Blommaert et al 1996;Husain et al 2001). These doses are equivalent to the clinical therapeutic doses of carboplatin in cancer patients (Bishop 1992;Bohm et al 1999;Wandt et al 1999;Maldoon et al 2000). However, administration of high and/or cumulative doses of carboplatin produced renal toxicity in humans (Agraharkar et al 1998;English et al 1999) and experimental animals (Ueda et al 1991;Martinez et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Male Wistar rats (2 months old, 250-300 g) were obtained from Charles River (Wilmington, MA, USA), divided into five groups and treated as follows: 1) control (normal saline 10 ml/kg, intraperitoneally (nΩ6); 2) carboplatin (64 mg/kg, intraperitoneally) (nΩ5); 3) carboplatin (128 mg/kg, intraperitoneally) (nΩ5); 4) carboplatin (192 mg/kg, intraperitoneally) (nΩ6); and 5) carboplatin (256 mg/kg, intraperitoneally) (nΩ8). The different doses of carboplatin used in this study correspond with clinical treatment protocols tried with this anticancer agent (Bishop 1992;Wandt et al 1999). The rats in all the groups were sacrificed by decapitation four days after treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28] Moreover, the source of haemopoietic progenitors (peripheral blood progenitors vs bone marrow) and the year of transplant (p1993 vs41993) were not associated with the outcome. The use of HGF (G-CSF or GM-CSF) after reinfusion of PBPC was associated with a significantly prolonged OS in both univariate and multivariate analysis (Table 3a, b).…”
Section: Discussionmentioning
confidence: 99%
“…1,[7][8][9][10][11][12] Our previous report on HDC in ovarian cancer showed encouraging results in terms of prolongation of time to progression and overall survival 12 and acceleration of hematopoietic recovery due to the combined administration of PBSC and growth factors. 13 Here, we report the updated results of the use of HDC 12 in a larger series of patients.…”
mentioning
confidence: 99%